Sistem Pengangkatan Presiden dalam Fikih Siyasah - Lukman Arake (Universitas Islam Negeri Jakarta, 2015)
The majority of Islamic scholars have argued that the president appoint a (Caliph) is obligatory. That is because human life can not possibly be a good, safe, prosperous and mutual respect between each other except in the presence of a leader. The presence of a leader is crucial understanding of living in a pluralistic community. This article examines the arguments concerning the obligation to appoint a leader, where there is a difference of opinion in terms of the mechanism of selection and appointment of a leader.DOI: 10.15408/ajis.v15i1.2847